The Protection of Health as a Duty of Care and as a Duty of Solidarity: Reflections about a Sustainable Health (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
The protection of health provided for in Article 32 of the Constitution has been subject to broad interpretation by the Constitutional Court, but, above all, to an extension by the legislator, who has interpreted the fundamental right to health in the light of the principles of equality and solidarity. Today, however, new problems are arising in the face of new technologies and greater availability of treatments, including expensive ones, which the National Health Service is nevertheless attempting to provide. The challenge is to protect everyone and to provide greater protection for vulnerable individuals, and the legislature, as well as the Constitutional court, seem to be converging on this perspective of integrated and supportive care and protection.
Keywords: rights; duties; solidarity; health; sustainability; vulnerability